PENGARUH KUALITAS PELAYANAN DAN KINERJA SUUPIR TERHADAP MINAT MENGGUNAKAN MODA TRANSPORTASI JAK LINGKO DI JAKARTA TIMUR - Yoka Mai Patria; Muhammad Tevin Anggahilal (Institut Ilmu Sosial dan Manajemen STIAMI, 2026)
This study aims to determine the effect of service quality and driver performance on interest in using Jak Lingko's services. In this paper, the writer uses a quantitative approach, with a sample of 100 people. Based on data obtained through the Jakarta Department of Transportation website, the average number of users on the Pulogadung – Harmoni route and vice versa is 11,574, with details of 13,576 users on weekdays (Monday – Friday) and 12,413 users on the weekend. The variables in this study include Service Quality, Performance, and Interest. The results of the study indicate that service quality and performance have a positive and significant effect on interest. However, the driver must take firm action to Jak Lingko transportation users in order to gain high trust from the public. Keywords service quality, performance, and interest